Novel multi-cover steganography using remote sensing image and general recursion neural cryptosystem - Zaidan, A.A.; Zaidan, B.B.; Taqa, Y.A.; Sami, M.K.; Alam, G.M.; Jalab, A.H. (Academic Journals, 2010)
Steganography is defined as the art of concealing a sensitive data through other carrier to insure the confidentiality of the data. Four novel concepts has been presented on this paper, beginning with steganography, the prevailing methods, well-known is the use of a single cover to hide the data, in this paper, we invent a new concepts on Steganography which is ``multi-cover steganography'' using remote sensing image; Remote sensing Image is an image taken from the satellite in a manner of three shots, engagimg these images generate one false color image, this type of image has been proposed in this research. The second concepts is general recursion neural cryptosystem, this approach has been designed and implemented to defeat the problem of exchange cryptography keys through the network, the new cryptosystem exchange the keys through trine the neural network data which later on used to decrypt the data, this powerful cryptosystem merged with the multi-cover steganography to produce the third novel concept. The fourth concept is designing irregular encoding method base on LSB algorithm. The new way of encoding has approved the security of data hidden. The experiment has approved that, our system has been extremely secure, confidential, and there is no way to extract the data from the cover